Symposium: Imaging modalities for drug-related osteonecrosis of the jaw (1), role of imaging in drug-related osteonecrosis of the jaw: An up-to-date review (secondary publication) - Makoto Tsuchimochi; Tohru Kurabayashi (Elsevier, 2019)
Summary: MRONJ/ARONJ is a serious adverse effect of medication, although the incidence of the disease is rare, and there are still controversial issues regarding the pathogenesis of MRONJ/ARONJ. Medications that can lead to MRONJ/ARONJ are commonly used to treat osteoporosis and to prevent bone fractures caused by bone metastasis of malignancies. The long-standing disease state of ONJ deteriorates the quality of life of affected patients. Early detection and prevention of the disease are key to alleviating pain and discomfort. To date, several imaging modalities have been introduced to depict the lesions. Imaging modalities, radiography, CT, MRI and nuclear medicine provide important information for managing this challenging disease. Keywords: MRONJ, ARONJ, BRONJ, Bisphosphonate, Imaging diagnosis,